Negligencia emocional y su efecto en el bajo rendimiento académico de una adolescente de 13 años en la Parroquia Catarama - González Moran, Sussetty Stefania (2023)
The negligence of one of the parents is a significant state in the emotional state of the adolescent who goes through these absences, where different alterations appear in the emotional, cognitive, and social areas. Currently, in this case study, the analysis of the 13- year-old adolescent student of the October 11 educational unit of the Catarama parish, based on an objective that is to determine emotional neglect and its effect on the academic area in the mentioned teenager. The main collection of information takes place a bibliographic exploration, with the focus of the two variables: emotional neglect and low academic performance. The patient comes to the consultation voluntarily, reports feelings of sadness, hopelessness, lack of interest in his activities, hypoprosexia. Psychological tests such as: Beck's depression inventory, family functioning, Rosenberg's self-esteem scale were used to evaluate the condition of the patient, this allowed evaluating the emotional state of the adolescent and establishing the traits of depression, some methods were also used such as psychological observation, semi-structured interview, clinical history. In addition, a presumptive diagnosis of recurrent depressive disorder with moderate episode 296.32 - F33.1 could be made according to the diagnostic criteria. Finally, the psychotherapeutic process using cognitive behavioral therapy was used. In short, it gave favorable results in the mental health of the pat